Oxaliplatin induces pH acidification in dorsal root ganglia neurons - Riva, Beatrice (Sci Rep, 2018)
Oxaliplatin induced peripheral neurotoxicity is characterized by an acute cold-induced syndrome characterized by cramps, paresthesias/dysesthesias in the distal limbs and perioral region, that develops rapidly and lasts up to one week affecting nearly all the patients as well as by long-lasting symptoms. It has been previously shown that pharmacological or genetic ablation of TRPA1 responses reduces oxaliplatin-induced peripheral neurotoxicity in mouse models. In the present report, we show that treatment with concentrations of oxaliplatin similar to those found in plasma of treated patients leads to an acidification of the cytosol of mouse dorsal root ganglia neurons in culture and this in turn is responsible for sensitization of TRPA1 channels, thereby providing a mechanistic explanation to toxicity of oxaliplatin. Reversal of the acidification indeed leads to a significantly reduced activity of TRPA1 channels. Last, acidification occurs also in vivo after a single injection of therapeutically-relevant doses of oxaliplatin.